Post-pandemic recovery strategies: revitalizing lifestyle entrepreneurship - Dias, Á.; Patuleia, M.; Silva, R. E.; Estêvão, J.; Martinez-Rodriguez, M. R. (Journal of Policy Research in Tourism, Leisure and Events, 2022)
The pandemic resulting from COVID-19 disease has brought about an unprecedented crisis to tourism destinations, resulting in an almost complete shutdown of tourist flows. Whereas disaster recovery models focus on prevention and preparedness, the post-pandemic recovery strategies are underexplored, particularly in relation to the highly representative group of small-scale businesses run by tourism lifestyle entrepreneurs (TLEs). An integrated framework for Destination Marketing Organization (DMO) strategic thinking is developed using the Delphi method with Q-sort technique. Findings from a 26-element expert panel emphasize the priority of creating a favorable environment for small-scale business development and supporting the provision of resources and capabilities. After this initial effort to strengthen these fragile businesses, it is essential to increase their communication capacity, a common limitation of TLEs, allowing these entrepreneurs to access niche markets more suited to the business and lifestyle they run. With stronger businesses, DMOs can enhance destination competitiveness and innovation, stimulating cooperation and networking.